Enjeux et conséquences de la réglementation sur le bois-énergie au Tchad - Ronan Mugelé (EchoGéo, 2013)
In 2008, in Chad, authorities implemented a new set of environmental regulation over the use and exploitation of woodfuels. Cutting wood and producing charcoal were declared illegal. This radical measure seems to obey to an ambivalent logic. On the one hand, it aims at fighting against desertification. On the other hand, it is used to enforce the State’s authority on the aftermath of major political troubles. The case-study of southern shores of Lake Chad reveals transformations in the dynamics of local power and resource exploitation, even though many places remain beyond the capacity of authorities to control.